Un regard différent sur les modèles d`apprentissage moteur présentés?: examen comparatif du modèle d`apprentissage moteur de Gallahue, Fitts et Posner et Ann Gentile - Salehi, S. K.; Tahmasebi, F.; Talebrokni, F. S. (Movement & Sport Sciences - Science & Motricité, 2021)
Learning motor skills follows a predictable sequence and stages. The main purpose of this study is to examine Gallahue`s motor learning model and compare it with existing featured models. Until now, several different models have been proposed by several theorists to identify and describe stages of motor learning. Fitts, P.M., and Posner, M.I. (1967. Human performance. Belmont: Brooks/Cole Pub. Co.) proposed a three-stage model for motor skill learning based on the learner`s cognitive state during the learning continuum. Gentile (1972-1978) proposed a two-stage model based on the goals of the learner. Gallahue (1972-2012) presented a three-level model with several accompanying sub-stages. In the present study, these models were compared in order to identify the best model to assist learners and practitioners. Analytical examinations showed that Gallahue`s motor learning model incorporates elements from both Fitts and Posner and Gentile models, but also provides specific guidelines and actions for instructors and practitioners along the learning continuum. Therefore, it seems to be more comprehensive and coherent (logical connection or relevant) in terms of functionality than existing models and provides specific cues for maximizing learning and meet the learner`s needs at each stage of learning.